ANALISIS INTEGRASI KEARIFAN LOKAL KOTA SAMARINDA DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN KESADARAN BUDAYA PESERTA DIDIK SEKOLAH DASAR - Zimmy Siringo-Ringo; Eko Handoyo; Indriana Eko Armaidi; Rhodentia Sri Hastuti Tamba (STKIP Subang, 2026)
Local wisdom is one of the important elements in contextual learning that can be used to strengthen the cultural identity of students in elementary school. This study aims to analyze the integration of local wisdom of Samarinda City in the learning of Natural and Social Sciences (IPAS) in order to increase the cultural awareness of elementary school students. The research uses a literature study method (library research) by examining various scientific sources in the form of journal articles, books, curriculum documents, and research results relevant to local wisdom, science learning, cultural identity, and Culturally Responsive Teaching (CRT). Data is analyzed through content analysis techniques which include data collection, reduction, organization, and interpretation. The results of the study show that the local wisdom of Samarinda City which includes Dayak, Kutai, Banjar, Erau traditions, Jepen dance, Horngang dance, Lamin traditional houses, beaded crafts, traditional food, as well as the value of mutual cooperation and environmental conservation have great potential to be integrated in IPAS materials. This integration can be done through the development of electronic teaching materials, project-based learning, exploration of the surrounding environment, and the Culturally Responsive Teaching (CRT) approach. The implementation of learning based on local wisdom is able to increase students' understanding of regional culture, foster a sense of pride in cultural identity, and strengthen cultural awareness in daily life. Therefore, the integration of local wisdom in social studies learning is an important strategy in realizing contextual education rooted in local culture.